(untitled) (Journal of the College of Basic Education, 2023)
Societies depend greatly for their growth and progress on their innovative minority, who are the ones whoThey paint a picture of the future for it, that this minority is in need of care and education from a young age. And it canIncreasing the number of innovators in a society by paying attention to the inherited innovative capabilities and developing someComplementary characteristics in early childhood.Taking care of the quality of life that innovators generally lead from childhood so that they do not loseThe community is on the road, but it is part of the appreciation and concern for the quality of life that the community leads.the whole of mankind.